2017
DOI: 10.1590/1678-7757-2016-0454
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physicochemical properties of root-end filling materials using conventional and Micro-CT tests

Abstract: Objective To evaluate solubility, dimensional stability, filling ability and volumetric change of root-end filling materials using conventional tests and new Micro-CT-based methods.Material and Methods 7 Results The results suggested correlated or complementary data between the proposed tests. At 7 days, BIO showed higher solubility and at 30 days, showed higher volumetric change in comparison with MTA (p<0.05). With regard to volumetric change, the tested materials were similar (p>0.05) at 7 days. At 30 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
52
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 27 publications
8
52
0
2
Order By: Relevance
“…Moreover, the higher solubility exhibited by Biodentine (Torres et al . ) may explain the delay in collagen formation as well as the maintenance of the accentuated FGF‐1 immunoexpression and number of mast cells in the Biodentine group at 60 days. The calcium chloride present in Biodentine liquid also may partially explain this delay.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the higher solubility exhibited by Biodentine (Torres et al . ) may explain the delay in collagen formation as well as the maintenance of the accentuated FGF‐1 immunoexpression and number of mast cells in the Biodentine group at 60 days. The calcium chloride present in Biodentine liquid also may partially explain this delay.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, similar filling ability was observed for S26 and ZOE, and both presented higher values than MTA. Torres et al 2 observed that ZOE presented better filling ability than MTA. Dias et al 19 observed that the modification of a composite resin with small amounts of zinc oxide (ZnO) microparticles significantly inhibited the S. mutans growth on resin surface without significant alterations of its mechanical strength.…”
Section: Discussionmentioning
confidence: 98%
“…Microcomputed tomography (micro-CT) is a non-destructive tool used for different studies in Endodontics as analysis of root canal filling 1 , filling ability of the reparative materials 2 and the evaluation of interface material/dentin associated with different root canal filling techniques and materials 3 . Micro-CT is also used for evaluating the volumetric change in endodontic materials, with possible correlation with solubility 4 and dimensional change after immersion in distilled water 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations